Shaping Natural History and Settler Society Mary Elizabeth Barber and the Nineteenth-Century Cape - Hammel, Tanja (Cambridge Imperial and Post-Colonial Studies, 2019)
"Hammel successfully illuminates how the production and circulation of Barber's work was deeply affected by contemporary attitudes towards gender and race within the colonial context of the nineteenth-century Cape. This fascinating book is destined to become a landmark in the history of science in South Africa." -Nigel Penn, University of Cape Town, South Africa "This book is an original study of the contributions of a woman scientist. It is the most detailed study of its kind...The book will make a significant addition to the global literature that examines the colonial and gendered dimensions of the history of science." -William Beinart, University of Oxford, UK "Moving seamlessly between biographical, local and international frames, this book provides a fresh look at the global knowledge transformations of the nineteenth century." -Kirsten McKenzie, University of Sydney, Australia This book explores the lifeand work of Mary Elizabeth Barber, a British-born settler scientist who lived in the Cape during the nineteenth century. It provides a lens into a range of subjects within the history of knowledge and science, gender and social history, postcolonial, critical heritage and archival studies. The book examines the international importance of a marginalized scientist, the instrumentalisation of science to settlers' political concerns and reveals the pivotal but largely silenced contribution of indigenous African experts. Including a variety of material, visual and textual sources, this study explores how these artefacts are archived in museums and critically analyses their content and silences. The book traces Barber's legacy across three continents, offering insights into the politics of memory and history-making. .